Prolyl hydroxylase substrate adenylosuccinate lyase is an oncogenic driver in triple negative breast cancer - Giada Zurlo (Nature Portfolio, 2019)
The hydroxylase EgIN2 contributes to triple negative breast cancers. Here, using an enzyme-substrate trapping strategy, the authors identify ASDL as a bona fide substrate of EgIN2 promoting aggressive properties of TNBC via the activation of cMYC signaling.